When Ulama Support A Pop Singer: Fatin Sidqiah and Islamic Pop Culture in Post-Suharto Indonesia - Akmaliah, Wahyudi (Al-Jamiah Research Centre, 2014)
Television, music videos, films, and pop bands are all part of global popular culture and thought to be the product of âthe westâ. These media are therefore often seen as a threat to the identities of nationalities, local cultures, and religious groups. In contrast, in the context of Indonesian Muslims, the Indonesian Ulama Councilâs (Majelis Ulama Indonesia, MUI) showed support for Fatin Shidqia Lubis to the singing contest of Indonesian X Factor, 2013. This paper intends to study the presence of Fatin Sidqiah as the winner of Indonesian X Factor and the response of Indonesian muslims regarding Islamic popular culture in Indonesia. This paper argues that the presence of Islamic popular culture in Indonesia through books, novels, films, as well as fashion, show that Indonesian Islam and muslims are compatible not only with democracy but also with global popular culture. In addition, the presence of Fatin is a symbol of young Indonesian muslims who already connect globally. Whatever they consume in terms of popular culture is intrinsic to the creation of their hybrid identities, as both Indonesian muslims and global citizens.[Televisi, musik, film, dan bands merupakan bagian dari budaya popular dunia dan selalu dipandang sebagai produk âbaratâ. Karenanya, media ini sering dianggap sebagai ancaman bagi identitas nasional, budaya lokal, dan kelompok agama. Namun, dalam konteks keindonesiaan, Majelis Ulama Indonesia (MUI) memberikan dukungan kepada Fatin Sidqia Lubis dalam kompetisi menyanyi âIndonesian X Factorâ Tahun 2013. Tulisan ini mencoba menelisik kemunculan Fatin sebagai pemenang âIndonesian X Factorâ dan tanggapan masyarakat mengenai budaya pop Islam di Indonesia. Melalui artikel ini penulis berpendapat bahwa kehadiran budaya pop di Indonesia dalam berbagai buku, novel, film, serta pakaian menunjukkan bahwa Islam dan masyarakat Islam di Indonesia tidak hanya sejalan dengan demokrasi, tetapi juga dengan budaya pop dunia. Lebih dari itu, Fatin adalah simbol muslim muda Indonesia yang telah terhubung dengan dunia. Apa pun yang mereka nikmati dalam hal budaya pop telah menciptakan identitas ganda: sebagai muslim Indonesia sekaligus sebagai warga dunia.]